Developing an IoT-Powered Sea Turtle Egg Incubator to Increase Survival Rate - Alex Surapati; Ade Sri Wahyuni; Gusta Gunawan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2026)
The turtle population in Pekik Nyaring Village, Bengkulu, is vulnerable to temperature, humidity, and predator threats when natural hatching methods are employed. Only around 50% of hatchlings successfully hatch as a result, and environmental instability and human exploitation are major factors. The goal of this project is to create an Internet of Things (IoT)-based egg incubator that uses an ESP32 microcontroller and a DHT22 sensor to monitor and regulate humidity (45–48%) and temperature (26–33°C) in real time. The system's WhatsApp notifications and integration with an IoT platform (Blynk) allow for remote monitoring and increase the effectiveness of sea turtle conservation initiatives. The gadget serves as an automated incubator that evaluates sensor efficacy and offers a technical solution that the community may readily embrace. A review of the literature on hatchling physiology, system design with block diagrams and hardware-software integration, sensor validation testing, system reaction tests, and field tests with 80 sea turtle eggs are all included in the study. Due to uneven heat distribution, restricted sand capillarity, local temperature rises brought on by incandescent bulbs, and sluggish water vapor diffusion processes within the media, the research results, while successful in hatching the eggs, were not ideal.